Implementasi Pendidikan Kewarganegaraan Dan Citizenship Education Longitudinal Study (CELS) Dalam Pembentukan Warga Negara Demokratis - Sari, Herdian Tria Wulan; Prianbudi, Dini Andreswari; Maulana, Ade Irfan; Wiranata, Irawan Hadi; Fauziah, Hamidah Ulfa (Jurnal Pendidikan Kewarganegaraan dan Politik, 2025)
Civic Education in Indonesia plays a strategic role in shaping democratic, active, and responsible citizens. This study focuses on the implementation of Civic Education in the Merdeka Curriculum and conceptually compares it with findings from the Citizenship Education Longitudinal Study (CELS). Using a qualitative descriptive method with a literature review approach, the study analyzes key sources on civic education and recent curriculum documents. The findings reveal that the Merdeka Curriculum integrates democratic values and human rights through project-based learning, the reinforcement of the Pancasila Student Profile, and the development of critical and collaborative thinking skills. Meanwhile, CELS highlights that contextual and continuous civic education significantly contributes to students' engagement in democratic processes. The study concludes that the integration of civic values into the curriculum, when supported by participatory learning strategies, has strong potential to cultivate empowered, democratic, and responsible citizensy.